Transcomplex epistemes of heritage knowledge in transmodernity: rhizomatic insights - Rodríguez, Milagros Elena (2020)
With comprehensive, diatopic and ecosophic hermeneutics as a transmethod of theoretical construction, epistemic theoretical axes of heritage knowledge framed in transmodernity are analyzed; understanding the interiority of heritage knowledge, culture, transcomplexity, cultural heritage, transmodernity, Transcomplex Heritage Education and ecosophy. In the final rhizome the patrimonial knowledge and the transmitted information do not capture all the meaning, the relationship of the patrimonial knowledge between subjects is intersubjective, a decolonization of them and their considerations based on citizenship and their identity is urgent, accepting that said knowledge involves complexity. Transcomplex Heritage Education configures a dynamic, emergent, related and relative process, where cultural heritage becomes more complex from learning, unlearning and relearning following the traces of heritage knowledge.